DASH transcription factor impacts Medicago truncatula seed size by its action on embryo morphogenesis and auxin homeostasis. (February 2015) - Noguero, Mélanie; Le Signor, Christine; Vernoud, Vanessa; Bandyopadhyay, Kaustav; Sanchez, Myriam; Fu, Chunxiang; Torres‐Jerez, Ivone; Wen, Jiangqi; Mysore, Kirankumar S.; Gallardo, Karine; Udvardi, Michael; Thompson, Richard; et al.
Summary The endosperm plays a pivotal role in the integration between component tissues of molecular signals controlling seed development. It has been shown to participate in the regulation of embryo morphogenesis and ultimately seed size determination. However, the molecular mechanisms that modulate seed size are still poorly understood especially in legumes. DASH (DOF Acting in Seed embryogenesis and Hormone accumulation) is a DOF transcription factor (TF) expressed during embryogenesis in the chalazal endosperm of the Medicago truncatula seed. Phenotypic characterization of three independent dash mutant alleles revealed a role for this TF in the prevention of early seed abortion and the determination of final seed size. Strong loss‐of‐function alleles cause severe defects in endosperm development and lead to embryo growth arrest at the globular stage. Transcriptomic analysis of dash pods versus wild‐type (WT) pods revealed major transcriptional changes and highlighted genes that are involved in auxin transport and perception as mainly under‐expressed in dash mutant pods. Interestingly, the exogenous application of auxin alleviated the seed‐lethal phenotype, whereas hormonal dosage revealed a much higher auxin content in dash pods compared with WT. Together these results suggested that auxin transport/signaling may be affected in the dash mutant and that aberrant auxin distribution may contribute to the defect in embryogenesis resulting in the final seed size phenotype.